The Colombo Public Library as a Reading Resource for Children in Colombo Metropolitan Area. - Athukorala, A.W.V. (the degree of Masters in Library and Information Science, 2008)
This study was carried out to assess the public library as a reading resource for children in Colombo Metropolitan Area. The Colombo public library has been selected on the site to conduct case study and survey method was used to collect the data. The population of the survey was staff, children under 14 years and their guardians attached to the Colombo public library. Stratified sampling was chosen for staff and purposive sampling was chosen for users and guardians. A questionnaire and structured interviews were administered for data collection in this research. The research seems to reveal that a children's library should be located at a point where the children would find easy access to it. A majority of students used the library belong to grade 7 and 9. Most of the students in the Colombo Metropolitan Area frequently use the children's library. The services such as inter library loans, documentation, government publications and audio visual services are not provided by the children's library. There seemed to have an imbalance in the distribution of library books among the Sinhala, Tamil and the English media. Although the number of periodicals available at the children's library is small, it is clear that these help improve knowledge, intelligence and appreciation of arts of children below 14 years of age. The major drawback in the collection of newspapers is that the lack of Tamil and English medium newspapers. The research seemed other than television programs no other extension services are provided by the library. It is an obstacle to the development of the moral, social and education skills among the children. The majority of readers are for reading child story books, translations and biographies. There are number of problems the juvenile readers face in of using the library. Although disabled users are not enrolled as members in the children's library, they are registered at the Book Box Project. Most of the students in urban schools within the Colombo Metropolitan Area frequently use the Book Box Project. The Book Box Project had not adapted any measures either for improving the reading of children or for increasing membership of the project. One of the major problems for readers was the unavailability of new books to the existing collection. The analysis is expected to be useful for the Colombo public library in upgrading library services and reading habits to the young users. The data will also be much useful for any library in formulation of library development programs and planning of new children's library development schemes for juvenile users.